Answer :

Given that x < 3 and y > 7

We have, y>7


Multiplying by (-) sign to the above inequality


As we know that the inequality sign changes when multiplied by (-) sign.


Therefore, -y<-7……..eq(1)


Also, x<3……..eq(2)


Now, adding eq(1) and eq(2).


We have, x-y< -4……….eq(3)


Again multiplying by (-) sign to the above inequality


We have, -(x-y) > 4………eq(4)


By taking mod of x-y, we can say that |x – y| > 4.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2

<span lang="EN-USKerala Board Mathematics Part-2